Frequency and outcome of sodium disturbances in children admitted with acute watery diarrhea in a tertiary hospital of Bangladesh - Ara , Ferdous; Mahmud, Nasir Uddin; Ul Quader, Mohammed Maruf; Amin Ahowdhury, Muhammad Jabed Bin; Tayeb Ali, Golam Mohammad; Sharmin, Tasnuva (Bangladesh Journal of Child Health, 2024)
Background: Acute watery diarrhea (AWD) is one of the common causes of hospital admissions in pediatric age group. Majority of children with dehydration suffer from different electrolyte abnormalities which needs to be identified and treated. Objectives: To investigate the frequency and outcome of sodium disturbances in AWD among children admitted in a tertiary hospital in Bangladesh. Method: In this prospective observational study, 121 children of 2 months to 5 years of age admitted in the Department of Pediatrics, Chittagong Medical College Hospital with AWD were included. Clinical features and sodium levels on admission were recorded. Patients were followed up during their hospital stay to record the outcomes. Children were grouped in hyponatremia (serum sodium <135mmol/l), hypernatremia (serum sodium >145mmol/l) and normonatremia (serum sodium 135–145mmol/l) and compared. Results: Of the 121 children, 38.0% and 62.0% had moderate and severe dehydration, respectively. The majority (58.7%) had normal sodium levels. Sodium disturbances was found in 41.3% cases. There were 26.4% cases of hypernatremia and 14.9% cases of hyponatremia among them. Out of 18 hyponatremic patients, 77.8% had mild hyponatremia and the rest 22.2% had moderate hyponatremia. Among 32 hypernatremic children, 62.4% had mild, 18.8% had moderate and 18.8% had severe hypernatremia. The case fatality rate was 2.6% and all of them had hypernatremic dehydration at admission. Conclusion: Sodium disturbances particularly hypernatremia is more frequent and is associated with high case fatality rate among children hospitalized with acute watery diarrhoea. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 110-114